Lost in Lexicon : an adventure in words and numbers - Noyce, Pendred (Lexicon adventure series, 2011)
When Aunt Adelaide sends thirteen-year-old cousins Ivan and Daphne on a treasure hunt in the rain, they never expect to stumble into a whole new world where words and numbers run wild.